Family Psychological Well-Being Is Reviewed From Gender And Education Level - Annisa Dianesti Dewi; Hanum Midya Syahrina; Laksmy Dewi Sukmakarti; Ayu Tri Arti; Wahyu Hanan Hapsari,; Permata Ashfi Raihana (Prosiding University Research Colloquium, 2021)
The family is the first unit related to a person's physical and psychological development.Therefore, the psychological well-being of the family becomes one of the benchmarks forthe welfare of the individual in it. The purpose of this study was to determineKesejahteraan psikologis at the family level in terms of gender and education level in earlyadulthood. The method used in this research is comparative quantitative. The subjects ofthis study were selected by purposive sampling and revealed 122 early adults on the islandof Java. This study uses a two-way Anova test to test the hypothesis. The results obtainedare: 1) there is no difference in the Kesejahteraan psikologis chosen by the family in termsof gender and early adult education level with p=0.372; 2) there are differences in theKesejahteraan psikologis of families in terms of gender with a significance value of 0.046and; 3) there is no difference in family Kesejahteraan psikologis in terms of education levelwith a significance of 0.246.